2012
DOI: 10.1073/pnas.1214605109
|View full text |Cite
|
Sign up to set email alerts
|

Pain relief produces negative reinforcement through activation of mesolimbic reward–valuation circuitry

Abstract: Relief of pain is rewarding. Using a model of experimental postsurgical pain we show that blockade of afferent input from the injury with local anesthetic elicits conditioned place preference, activates ventral tegmental dopaminergic cells, and increases dopamine release in the nucleus accumbens. Importantly, place preference is associated with increased activity in midbrain dopaminergic neurons and blocked by dopamine antagonists injected into the nucleus accumbens. The data directly support the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
270
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(302 citation statements)
references
References 47 publications
24
270
0
4
Order By: Relevance
“…The results presented might thus be explained by a capsaicin-induced enhancement of thermal gating of TRPV1 expressed in polymodal nociceptors mediating thermal pain sensation (Carstens et al, 2007;Albin et al, 2008). However, we do not exclude the possibility that, in the two-temperature preference tests, the rats prefer the cool side because they are seeking alleviation of the 'burning' pain (De Felice et al, 2013;Navratilova et al, 2012Navratilova et al, , 2013) that can be specified on the modulation of TRP channel sensitivity. Hoffmann et al (2013) have recently shown that TRPA1 and TRPV1 channels contribute to thermal nociception, and that both TRPA1 and TRPV1 null mice presented behavioral deficits in heat sensitivity.…”
Section: Discussionmentioning
confidence: 67%
“…The results presented might thus be explained by a capsaicin-induced enhancement of thermal gating of TRPV1 expressed in polymodal nociceptors mediating thermal pain sensation (Carstens et al, 2007;Albin et al, 2008). However, we do not exclude the possibility that, in the two-temperature preference tests, the rats prefer the cool side because they are seeking alleviation of the 'burning' pain (De Felice et al, 2013;Navratilova et al, 2012Navratilova et al, , 2013) that can be specified on the modulation of TRP channel sensitivity. Hoffmann et al (2013) have recently shown that TRPA1 and TRPV1 channels contribute to thermal nociception, and that both TRPA1 and TRPV1 null mice presented behavioral deficits in heat sensitivity.…”
Section: Discussionmentioning
confidence: 67%
“…This is the first study to report a pain-related and analgesic-reversible decrease in microdialysis measures of NAc DA after treatment with a noxious stimulus. However, two other recent studies reported increases in NAc DA release after antinociceptive treatments in rat models of postsurgical or cephalic pain (De Felice et al, 2013;Navratilova et al, 2013). This preclinical evidence for reciprocal effects of pain-and analgesia-related manipulations on NAc DA corresponds to clinical evidence from functional magnetic resonance imaging studies for reciprocal negative/positive signals in NAc at pain onset/offset, respectively (Becerra and Borsook, 2008).…”
Section: Pain-related Depression Of Mesolimbic Da Releasementioning
confidence: 99%
“…This suggests that also in rats changes in the relative timing of cue and punishment do more than affecting whether and how much learning occurs, but rather can affect the valence of the respective mnemonic effect (for a related finding see also Smith and Buchanan 1954). A different approach was used by Navratilova et al (2012): The authors investigated tonic post-surgical pain and induced relief by pharmacological treatment of that pain. Using a place preference/avoidance apparatus, such treatment was paired with one compartment of the apparatus whereas the other compartment was paired with a placebo treatment.…”
Section: Rat Punishment-learningmentioning
confidence: 99%
“…1) (we use "relief" to refer specifically to the acute effects of punishment offset; an equally legitimate yet broader use of the word in, e.g., "fear relief," encompasses any process that eases fear [Riebe et al 2012]). Indeed, in experimental settings, it turns out that stimuli experienced before and during a punishing episode are later avoided as they signal upcoming punishment, whereas stimuli experienced after a painful episode can subsequently prompt approach behavior, arguably (Box 1) because of their association with the relieving cessation of pain (Konorski 1948;Smith and Buchanan 1954;Wolpe and Lazarus 1966;Zanna et al 1970;Solomon and Corbit 1974;Schull 1979;Solomon 1980;Wagner 1981;Walasek et al 1995;Tanimoto et al 2004;Yarali et al 2008Yarali et al , 2009bAndreatta et al 2010Andreatta et al , 2012Yarali and Gerber 2010;Ilango et al 2012;Navratilova et al 2012;Diegelmann et al 2013b); for a corresponding finding in the appetitive domain, see Hellstern et al (1998) and Felsenberg et al (2013). Such relief can both support the learning of the cues associated with the disappearance of the threat and reinforce those behaviors that helped to escape it.…”
mentioning
confidence: 99%